1990
DOI: 10.1104/pp.94.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Methane Transport from the Rhizosphere to the Atmosphere through Rice Plants

Abstract: To clarify the mechanisms of methane transport from the rhizosphere into the atmosphere through rice plants (Oryza sativa L.), the methane emission rate was measured from a shoot whose roots had been kept in a culture solution with a high methane concentration or exposed to methane gas in the gas phase by using a cylindrical chamber. No clear correlation was observed between change in the transpiration rate and that in the methane emission rate. Methane was mostly released from the culm, which is an aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
176
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(183 citation statements)
references
References 22 publications
5
176
0
2
Order By: Relevance
“…Such technical approach is suitable for microcosm experiments, but can hardly be used for field studies. Since rice plants allow the transport of O 2 from the atmosphere into the soil and of CH 4 from the soil into atmosphere via their gas vascular system and aerenchyma tissue in roots and shoots by a diffusional process (Nouchi et al, 1990;Schü tz et al, 1991), we inferred that transport of 13 C-labelled CH 4 from the atmosphere into the rhizosphere is also possible and that rhizospheric methanotrophs can be labelled in this way. The transport of 13 C-labelled CH 4 from the atmosphere into the rhizosphere was indeed operating as shown by the incorporation of 13 C into microbial PLFAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such technical approach is suitable for microcosm experiments, but can hardly be used for field studies. Since rice plants allow the transport of O 2 from the atmosphere into the soil and of CH 4 from the soil into atmosphere via their gas vascular system and aerenchyma tissue in roots and shoots by a diffusional process (Nouchi et al, 1990;Schü tz et al, 1991), we inferred that transport of 13 C-labelled CH 4 from the atmosphere into the rhizosphere is also possible and that rhizospheric methanotrophs can be labelled in this way. The transport of 13 C-labelled CH 4 from the atmosphere into the rhizosphere was indeed operating as shown by the incorporation of 13 C into microbial PLFAs.…”
Section: Discussionmentioning
confidence: 99%
“…The total emission of CH 4 from Chinese rice fields was estimated to be in the range of 8.05 ± 3.69 Tg CH 4 per year, depending on the type of rice paddy field (Cai, 1997). In these ecosystems, the main CH 4 emission to the atmosphere occurs through the aerenchyma system of the rice plants (Nouchi et al, 1990;Schü tz et al, 1991). In turn, oxygen from the atmosphere is transported to the rice roots enabling aerobic and microaerophilic conditions in the rhizosphere .…”
Section: Introductionmentioning
confidence: 99%
“…In flooded rice fields the methane produced in deeper layers is mainly emitted by vascular transport through the rice plant and by bubbling to the atmosphere (Holzapfel-Pschom et al, 1985;Nouchi et al, 1990). Since the vascular system of rice plants also transports oxygen into the soil, the rice field soil becomes a complex structure containing oxic and anoxic zones (Armstrong, 1979;Frenzel et al, 1992).…”
mentioning
confidence: 99%
“…Cyperus papyrus (Li & Jones, 1995) and Peltandra virginica (Frye, Mills & Odum, 1994). A different ecological pattern occurs in J. effusus (this study) and rice (Nouchi, Mariko & Aoki, 1990) with greater methane concentrations in leafy shoots during the day than at night.…”
Section: mentioning
confidence: 98%
“…For example, Nouchi et al (1990) demonstrated that methane leaks from the culm (aggregation of leaf sheaths) of rice through small micropores that do not undergo opening and closing like stomata. This observation helps explain why methane does not accumulate within rice plants overnight.…”
Section: mentioning
confidence: 99%